Gypenosides Alleviate Hyperglycemia by Regulating Gut Microbiota Metabolites and Intestinal Permeability - Rong Wang; Xue-Feng Liu; Kuan Yang; Li-Li Yu; Shao-Jing Liu; Na-Na Wang; Yun-Mei Chen; Ya-Qi Hu; Bei Qin (Current Issues in Molecular Biology)
Background/Objectives: Gypenosides (Gps) are the main active compounds of Gynostemma and show promise in managing diabetes; nevertheless, the mechanism by which Gps exert anti-diabetic effects is still not fully understood. The aim of this study is to clarify the molecular mechanisms of Gps in ameliorating glucose dysregulation. Methods: Qualitative and quantitative analyses on the chemical components of Gps were performed, respectively. Type 2 diabetes mellitus mouse models were established, and the mice were subsequently treated with Gps at doses of 200, 100, or 50 mg/kg for 4 weeks. Biochemical markers were measured. Histopathological assessments of hepatic and colonic tissues were conducted. The compositions of the intestinal microbiota, short-chain fatty acids (SCFAs), and bile acids (BAs) in fecal samples were analyzed. Western blotting was applied to examine the activation of relevant signaling pathways. Results: Gps have potent regulatory effects on metabolic homeostasis by improving glucose and lipid profiles and alleviating hepatic tissue damage. Treatment with Gps significantly reduced serum levels of lipopolysaccharides and key pro-inflammatory cytokines (interleukin-6 and tumor necrosis factor-α). Moreover, Gps enhanced the integrity of the gut barrier by upregulating the level of tight junction proteins (ZO-1 and occludin). Microbiota profiling revealed that Gps markedly increased microbial diversity and richness, decreased the ratio of Firmicutes/Bacteroidetes, and elevated Bacteroidia abundance from the phylum to the genus level. Targeted metabolomics further demonstrated that Gps modulated gut microbial metabolites by promoting SCFA production and reshaping BA profiles. Specifically, Gps elevated the primary-to-secondary BA ratio while reducing the 12α-hydroxylated to non-12α-hydroxylated BA ratio. Mechanistically, Western blotting demonstrated that Gps triggered the hepatic PI3K/AKT pathway and the intestinal BA/FXR/FGF15 axis, suggesting the coordinated regulation of metabolic and gut–liver axis signaling pathways. Conclusions: Gps significantly ameliorate hyperglycemia and hyperlipidemia through a multifaceted mechanism involving gut microbiota modulation, the restoration of intestinal barrier function, and the regulation of microbial metabolites such as SCFAs and BAs. These findings offer novel insights into their mechanism of action via the gut–liver axis.